Initial Response and Outcome of Critically Ill Children With Guillain Barre' Syndrome - Bazaraa, Hafez M.; Rady, Hanaa I.; Mohamed, Shereen A.; Rabie, Walaa A.; ElAnwar, Noha H. (Frontiers in Pediatrics, 2019)
Background: Guillain-Barre syndrome is the most common cause of acute flaccid paralysis worldwide since the eradication of poliomyelitis. Severe cases may require intensive care and mechanical ventilation. Purpose: was to study pediatric patients with severe GBS requiring intensive care unit (ICU) admission, to assess their course and response to initial treatment modality plasma exchange (PE) or intravenous immunoglobulins (IVIg) and their final outcome. Methods: children with severe GBS who had either actual or impending respiratory failure, bulbar involvement or rapid progression of acute flaccid paralysis with trunk, upper limb and neck involvement within 24 hours of the onset of weakness were enrolled. Results: 40 children were included. Following the initial treatment (33 subjects had 5 PE sessions each and IVIg in 7), 16 patients improved (40%), two died and 22 (55%) showed initial treatment failure. Axonal neuropathy, rapid progression and severe motor weakness significantly predicted poor response to therapy. At discharge, favorable outcomes (patient can walk unaided) were present in 22 cases (58%). Conclusion: Despite relatively low mortality, critically ill children with severe GBS have increased prevalence of axonal neuropathy and guarded response to initial therapy with PE or IVIg.